Operating systems : design and implementation - Tanenbaum, Andrew S., 1944-; Woodhull, Albert S. (Upper Saddle River, NJ : Prentice Hall, 1997)
The Second Edition of this best-selling introductory operating systems text is the only textbook that successfully balances theory and practice. The authors accomplish this important goal by first covering all the fundamental operating systems concepts such as processes, interprocess communication, input/output, virtual memory, file systems, and security.
These principles are then illustrated through the use of a small, but real, UNIX-like operating system called MINIX that allows students to test their knowledge in hands-on system design projects. Each book includes a CD-ROM that contains the full MINIX source code and two simulators for running MINIX on various computers.
1. Introduction -- 2. Processes -- 3. Input/Output -- 4. Memory Management -- 5. File Systems -- 6. Reading List and Bibliography -- App. A. MINIX Source Code Listing -- App. B. Index to Files -- App. C. Index to Symbols.
Includes bibliographical references and index.
Keywords: Operating systems (Computers)